Total synthesis of (S)-(+)-melodorinol and (S)-(+)-acetylmelodorinol - Manat Pohmakotr (2018)
(S)-(+)-Melodorinol and (S)-(+)-acetylmelodorinol have been synthesized by reacting the lithiated butenolide with 2,3-O-alkylidene-D-glyceraldehyde followed by successive elimination, hydrolysis, benzoylation and acetylation reactions.